The psychosocial indicators related to neuroticism in both sexes: A study of incoming university students. Issue 4 (31st January 2015) - Chang, Wei‐Hung; Cheng, Shu‐Hui; Sun, Zih‐Jie; Lee, I‐Hui; Lee, Chih‐Ting; Chen, Kao‐Chin; Tsai, Chung‐Hung; Yang, Yen‐Kuang; Yang, Yi‐Ching
Abstract: Neuroticism may have great impact on mental and physical health in both sexes. The aims of this study were to explore whether relationships between neuroticism scores and psychosocial indicators as well as metabolic syndrome in a population of incoming university students existed in the different sexes. In total, 4266 incoming students were included in this study. The test battery comprised a self‐administered structured questionnaire, including the neuroticism subscale of the Maudsley Personality Inventory, the 12‐item Chinese Health Questionnaire, the Chinese Internet Addiction Scale‐Revision, the measurement of support functions, and the Pittsburgh Sleep Quality Index. Multivariate logistic regression showed that higher Pittsburgh Sleep Quality Index scores, higher Chinese Internet Addiction Scale‐Revision scores, and higher 12‐item Chinese Health Questionnaire scores were significantly correlated with neuroticism in both sexes, but lower perceived routine support: measurement of support functions scores were associated only with the male participants. No significant differences were found in terms of body mass index or other metabolic profiles. Individuals with poorer mental health and a poorer personal lifestyle had higher neuroticism scores, and sex effects may influence the scale of perceived social support in the neuroticism group. However, the lack of an association between neuroticism score and metabolic syndrome may be due to the recruitment of younger participants in this study.